FAKTOR-FAKTOR YANG MEMPENGARUHI IMPOR GULA PASIR DI INDONESIA TAHUN 1980-2010 - Yayan Sukma Wiranata (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2014)
Sugar is one of the essential commodities and is a strategic food commodity after rice. As a country with the resources agribusiness, Indonesia has become one of the major producer and exporter of sugar in the world’s largest in the 1930s and 1940s. But along with the declining productivity of sugar in the country, a title as sugar exporting countries that have carried Indonesia has now turned into a net importer of sugar is quite large. That’s because the amount of domestic sugar production which tends to decrease each year which resulted in insufficient demand of consumption of sugar so that the steps taken by the government to be able to meet the need of domestic sugar is to import sugar. This study aimed to determine the effect of independent variables (population, production of sugar and sugar consumption) on the dependent variable (sugar imports) in both the short and long term.This study uses time series data. The analysis model used is the econometric analysis tool error correction model (Error Correction Model / ECM). This model can explain the behavior of short and long term.The results showed (1) a variable number of the population in the short and long term there is no effect on sugar imports. (2) the variable consumption of sugar in the short term and the long term there is no effect on sugar imports. (3) Variable production of sugar in the short term there is the influence of the sugar imports, while in the long term there is no effect between sugar production with imported sugar.Based on these results it can be concluded that the variables of population, the consumption of sugar and sugar production in the long term no significant effect on sugar imports, while in the short term only sugar production variables that affect the import of sugar. Domestic sugar production to be increased to meet the needs of domestic sugar that can be imported controlled.